The Growth of Sodic Amphibole at the Greenschist- to Blueschist-facies Transition (Dent Blanche, Western Alps): Bulk-rock Chemical Control and Thermodynamic Modelling. (20th March 2020) - Manzotti, Paola; Ballèvre, Michel; Pitra, Pavel; Putlitz, Benita; Robyr, Martin; Müntener, Othmar
Abstract: The sodic amphibole glaucophane is generally considered as indicative of blueschist-facies metamorphism. However, sodic amphiboles display a large range in chemical compositions, owing principally to the Fe 2+ Mg–1 and Fe 3+ Al–1 substitutions. Therefore, the whole-rock composition (namely its Na2 O and FeO* content, and the Fe 2+ –Fe 3+ ratio), strongly controls the stability field of the sodic amphiboles at the transition from greenschist- to blueschist-facies conditions. Neglecting these variables can lead to erroneous estimates of the metamorphic conditions and consequently the tectonic framework of the rocks. This paper explores the mechanisms that control the development of sodic amphibole and sodic pyroxene within the basement of the Dent Blanche Tectonic System (Western Alps), as a result of the Alpine metamorphic history. Field, petrographic and geochemical data indicate that sodic amphibole and sodic pyroxene form in different rock types: (1) in undeformed pods of ultramafic cumulates (hornblendite), sodic amphibole (magnesioriebeckite) forms coronas around magmatic pargasite; (2) metatonalite displays patches of radiating sodic (magnesioriebeckite) and calcic (actinolite) amphiboles; (3) sodic amphibole (magnesioriebeckite–glaucophane) occurs with high-Si potassic white mica (phengitic muscovite) in fine-grained (blue) schists; (4) in mylonitized granitoids (amphibole-gneiss) metasomatized along the contact with ultramafic cumulates, sodic amphibole (magnesioriebeckite–winchite) mainly forms rosettes or sheaves, generally without a shape-preferred orientation. Only locally are the needles aligned parallel to the stretching lineation. Pale green aegirine–augite is dispersed in an albite–quartz matrix or forms layers of fine-grained fibrous aggregates. The bulk-rock chemical composition of the different lithologies indicates that sodic amphibole and sodic pyroxene developed in Na- and Fe-rich systems or in a system with high Fe 3+ /Fe*. Thermodynamic modelling performed for different rock types (taking into account the measured Fe2 O3 contents) reveals that sodic amphibole appears at ∼8 ± 1 kbar and 400–450 °C (i.e. at the transition between the greenschist- and blueschist-facies conditions) about 5 kbar lower than previous estimates. To test the robustness of our conclusion, we performed a review of sodic amphibole compositions from a variety of terranes and P – T conditions. This shows (1) systematic variations of composition with P – T conditions and bulk-rock chemistry, and (2) that the amphibole compositions reported from the studied area are consistent with those reported from other greenschist- to blueschist-facies transitions.